Endometrial Volume, and Sub-Endometrial Blood Flow Indices as Predictors of ICSI Success - Wessam M. Abuelghar; Abdelatif G. Elkholy; Ibrahim A. Abdelazim; Ihab Serag; Kahaled I Abdallah; Mohamed M. Ahmed (Medical Network, 2018)
Objective: This study designed to evaluate the endometrial volume, and the sub-endometrial flow indices as predictors of ICSI success. Study Design: Fifty infertile women included in this study, and received long pituitary downregulation protocol followed by hMG controlled hyperstimulation until ≥ 3 ovarian follicles 18-20 mm in diameter detected. Ovulation triggered by hCG, followed by oocytes retrieval 34-36 hours after hCG trigger. Day 2 or 3 embryo transfers done for all studied women, followed by quantitative β-hCG 14 days after the embryo transfers, and transvaginal sonography to diagnose clinical pregnancy. Studied women evaluated by the 3D ultrasound, and 3D power Doppler angiography at the day of the embryo transfers to assess the endometrial volume, and the sub-endometrial flow indices as predictors of the ICSI success. Results: The endometrial volume, sub-endometrial vascularization index, flow index, and vascularization flow index were higher in successful ICSI compared to unsuccessful ICSI group, but the difference was not significant. The ROC analysis showed that the endometrial volume and the 3D power Doppler angiography parameters (vascularization index, flow index, and vascularization flow index indices) were not conclusive for prediction of successful clinical pregnancy after the current ICSI trials. Conclusion: The endometrial volume and the 3D power Doppler angiography indices were not predictive for the clinical pregnancy after the current ICSI trials.